Developing Written News Item Text Materials for the Tenth Graders of Senior High School - Muryati, Sri (Register Journal, 2013)
School Based Curriculum or âKurikulum Tingkat Satuan Pendidikanâ (KTSP) 2008 requires teaching and learning activities that should be active, innovative, creative, enjoyable, cheerful and qualified. In order to share or help teachers, this Research and Development (R&D) research was conducted that may inspire them in developing teaching and learning materials for the expected class. The scope of this study is developing written news item text materials for the ten graders of senior high school so that the students are able to create a simple short news item texts which are classified into four kinds: straight, interpretative, investigative and color news stories. The method used was adapted and adjusted from Hylandâs Model of material development. The process started from doing a survey, followed by developing materials, having experts and teachers validation, doing first revision, trying out, writing second revision, and producing final result. The try out resulted student average score 76,14 that means the students achieved 79,55 % above minimum national learning mastery, 75. This study focuses on the written news item texts from the 3 sources, namely newspapers, magazine and internet. Since the three sources are available in one source, the internet, the final product is entitled â3 News in 1â accompanied by Interactive Self-study VCDâ.Â Keywords: R&D; News item texts;Â  teaching & Learning materials.Â